The Dynamics of Livelihood Vulnerability Index at Farm Household Level: An Empirical Analysis of the Coastal Sandy Zone in Thua Thien Hue Province, Vietnam - Minh, Dao Duy; Lebailly, Philippe; Hao, Nguyen Dang; Burny, Philippe; Hop, Ho Thi Minh (International Journal of Economics and Financial Issues, 2019)
Rural households in Vietnam have been facing various adverse impacts on their livelihoods. By using 28 indicators of Sustainable Livelihood Framework (SLF), this study aims to identify the Livelihood Vulnerability Index (LVI) of the households in the coastal sandy zone in Thua Thien Hue (TTH). Based on the baseline data in 2007-2008, the study conducted a survey of 110 households living in four districts of the region to have a thorough evaluation of LVI. The results showed that excluding the increase in natural capital index (0.194 to 0.225), the value of LVI reduced in the dimension of human capital (0.365 to 0.363), social capital (0.081 to 0.075), physical capital (0.139 to 0.048) and financial capital (0.405 to 0.273). In overall, the value of the LVI index scored 0.244 in 2007-2008 and 0.214 in 2017-2018, respectively. The research findings contribute a deeper understanding of the vulnerable context of household communities that support the issuance of policy intervention, a social project as well as impact assessment of the given factors such as change of vulnerable contexts, structure and process. Keywords: Empirical Analysis, Farm Households, Rural Development JEL Classifications: D120; Q120, R 580 DOI: https://doi.org/10.32479/ijefi.8250